Percepción de mujeres trans sobre el acceso al empleo en la ciudad de Lima en los años 2015 – 2020: la entrevista de trabajo como espacio productor de derechos rancios - Pérez Díaz, Kenny Jorge (2024)
The objective of this research is to analyze the perception of trans women related to the access to formal employment in the city of Lima. Thus, we will reflect on the sociocultural patterns and how they make us read our bodies. Those patterns oppress, punish and even annul the condition of human being to a person who has a diverse body practice, such as trans women. Throughout the research we will detail that, even with the process of feminization, trans women feel that they will be discriminated in job interviews due to the canon of sexual difference present in the mental schemes of the interviewers. The method used was participant observation and semi-structured interviews with trans women who voluntarily agreed to provide information to theorize about their perceptions. The results reveal that the spaces of job interviews are producers of limitations to their human rights, especially the right to work in the variant of access to employment.